Efficacy of Sanhua essential oil inhalation in patients with breast cancer-related depression undergoing chemotherapy: A randomized, single-masked, placebo-controlled clinical trial - Xiaofei Li; Zehui Xu; Mengting Dong; Yuelian Wang; Xinyue Zhou; Ke Jiang; Jiayu Sheng (Journal of Traditional Chinese Medical Sciences, 2025)
Objective: To evaluate the efficacy of Sanhua essential oil inhalation as aromatherapy in patients with breast cancer-related depression. Methods: In total, 144 patients with breast cancer-related depression who underwent postoperative chemotherapy were recruited. The participants in the control group (n = 52) were offered a placebo (sunflower oil) daily, whereas those in the essential oil group (n = 52) were administered Sanhua essential oil. This study evaluated depression improvement, Hamilton Depression Scale score, scores of symptoms in traditional Chinese medicine (TCM), Pittsburgh Sleepiness Quotient Index score, incidence of nausea and vomiting, and signal changes on functional magnetic resonance imaging. Results: Depression improved by 48.1% and 21.2% in the essential oil and control groups, respectively (P = .010). The Hamilton Depression Scale score (P = .017), scores for symptoms in TCM (P = .002), and the incidence of nausea and vomiting in the acute and delayed phases were lower in the essential oil group than in the control group (nausea in the acute phase, P = .017; nausea in the delayed phase, P = .039; vomiting in the acute phase, P = .008; vomiting in the delayed phase, P = .081). The Pittsburgh Sleepiness Quotient Index score was lower in the essential oil group than in the control group (P = .005). Significant differences existed between the two groups in the left superior parietal gyrus, right precuneus, left dorsolateral superior frontal gyrus, and right precentral gyrus according to functional connectivity on functional magnetic resonance imaging. Conclusion: Inhalation of Sanhua essential oil alleviated depression in patients undergoing chemotherapy for breast cancer, improved sleep quality, relieved TCM symptoms, reduced nausea and vomiting, and regulated activities in the brain regions.